1991
DOI: 10.1080/02626669109492485
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the response of a water table to a variable recharge rate

Abstract: A new method of evaluation of the response of a water table to artificial recharge is presented. The solution is formulated in the form of a simple numerical model. The model has several advantages over the traditional methods of mounding prediction. The effect of the unsaturated zone, which modifies the recharge rate as compared with the infiltration rate, is considered. Mounding is calculated for a variable recharge rate induced by a variable infiltration rate. Also, the effect of in-transit water in reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 24 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…The transient rate of recharge is usually approximated by an exponential function or multiple linear elements (Zomorodi 1991;Rai and Manglik 1999). In this section, we define a cycle of recharge as follows:…”
Section: Cycle Of Time Varying Rechargementioning
confidence: 99%
“…The transient rate of recharge is usually approximated by an exponential function or multiple linear elements (Zomorodi 1991;Rai and Manglik 1999). In this section, we define a cycle of recharge as follows:…”
Section: Cycle Of Time Varying Rechargementioning
confidence: 99%
“…However, for short term recharge operations such as intermittent recharge or flood spreading, it would be more appropriate to consider time varying recharge to simulate the real field conditions with more accuracy. Zomorodi (1991) has shown that the analytical solution given by Dagan (1966) for constant rate of recharge failed to predict the declining trend of water table which is caused by a decrease in the rate of recharge. Rai et al (1994), Singh (1995, 1996), Rai et al (1998); Ramana et al (1995) have presented analytical solutions of linearized Boussinesq equation to describe water table fluctuation in response to time varying recharge.…”
Section: Introductionmentioning
confidence: 95%
“…After drying and, if necessary, scrapping of the silted bottom of the basin high recharge rate closer to its initial value is rejuvenated again in the next phase of recharge operation (Bear, 1979;Detay, 1995;Mousavi and Rezai, 1999). Zomorodi (1991) has shown that the analytical solution of Dagan (1966) which is based on the assumption of constant recharge rate failed to predict the recession of the water table caused by a decrease in the recharge rate. Pumping of ground water is carried out at different times when need for irrigation arises.…”
Section: Introductionmentioning
confidence: 96%